Improving the effectiveness of the educational process in physical education of students using balancing platforms - Melnikova, T.I.; Vinogradova, O.P.; Butakova, E.D. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to increase the effectiveness of physical education electives by introducing the training functionality of BOSU universal balancing platforms into the educational process. Methods and structure of the study. Sports and pedagogical testing of the physical and technical conditions of 56 female students aged 18 to 20 was carried out, factors of the effectiveness of the educational process in physical education were identified, teachers were interviewed, followed by a pedagogical experiment using BOSU balancing platforms. Results and conclusions. The effectiveness of the developed training complexes using balancing platforms is proved by the results of a pedagogical experiment. The achievements of all control tests significantly improved (p<0.05), the largest increase in indicators was shown in the balance test. The number of female students who completed the technical test for the highest score increased by 30.7%. Exercises on a balancing platform can be considered as a universal training tool aimed at solving the complex tasks of physical education of students of managerial specialties.